Setting up Vocational Qualification Set up for Competency Based Education for People at Work - Mali, Milind S.; Mandke, Vijay V. (Journal of Engineering Education Transformations, 2006)
With the onrush of "Technology" at work places and with issues of productivity, cost-effectiveness, needs of sustained development and competitiveness in industries, the requirement of continuing education and professional development of those in work is fast becoming central to survival and growth of any national and regional industrial sector. This essentially is the question of linking education-training, as the acquisition of knowledge through the educational process needs to be dovetailed with specifics of training for a particular technology and particular work place, where only index of attainment of training objective is if the learner can actually "do" the job. The Vocational Qualification (VQ) Set Up as visualized through this project proposal is essentially a step in the above direction.